The effect of Murabahah Financing BMT UGT Sidogiri on the Welfare of Reni Jaya Market Traders Depok city, west java - Hardilah Pausiyanti; Nur S Buchori; Nursanita Nasution (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
The purpose of this study was to determine the effect of murabahah financing of BMT UGT Sidogiri on the welfare of traders at Reni Jaya Market, Depok City, West Java. This research is quantitative research with a causal approach. The data used are primary data obtained by distributing questionnaires to 112 respondents at the Reni Jaya market in Depok. Barokah Business Capital Products (MUB) BMT UGT Sidogiri, especially murabahah financing, the trend of murabahah financing members and murabahah financing income for 5 years, namely before the Covid-19 pandemic starting in 2017-2019 experienced an increase, as well as during the Covid-19 pandemic starting from 2019-2021 successively increased. While the data analysis technique used in this research is using descriptive statistics with the SPSS application. The results showed that the Murabahah Financing of BMT UGT Sidogiri had a significantly positive effect on Micro, Small and Medium Enterprises (Y) with a significant value of 0.000 0.05.